2015
DOI: 10.1002/cbm.1977
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic violence and readiness to change among male intimate partner violence offenders

Abstract: Background Although readiness to change is associated with mandated partner violence treatment compliance and subsequent violent behavior among male offenders (e.g., Eckhardt et al., 2004; Scott & Wolfe, 2003), our understanding of the factors associated with pretreatment change remains limited. Offender research indicates that individual and dyadic violent behavior are highly variable and that such variability may provide insight into levels of pretreatment change (Archer, 2002; Holtzworth-Monroe & Stuart, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This is an important concern and challenge for the reduction and prevention of IPV, since program dropout is associated with higher recidivism rates (Bennett et al, 2007;Chen et al, 1989;Coulter & VandeWeerd, 2009;Dutton et al, 1997;Gondolf, 2000;Taft et al, 2001). Additionally, IPV offenders typically show low levels of motivation to change at the intake phases of IPV offender programs Crane et al, 2015;Zalmanowitz et al, 2013). This is an important issue, because IPV offenders in the most advanced stages of change are more likely to complete the treatment (Eckhardt et al, 2004;Levesque et al, 2000;Scott, 2004;Scott & Wolf, 2003).…”
Section: Las Estrategias Motivacionales En Las Intervenciones Con Agrmentioning
confidence: 99%
“…This is an important concern and challenge for the reduction and prevention of IPV, since program dropout is associated with higher recidivism rates (Bennett et al, 2007;Chen et al, 1989;Coulter & VandeWeerd, 2009;Dutton et al, 1997;Gondolf, 2000;Taft et al, 2001). Additionally, IPV offenders typically show low levels of motivation to change at the intake phases of IPV offender programs Crane et al, 2015;Zalmanowitz et al, 2013). This is an important issue, because IPV offenders in the most advanced stages of change are more likely to complete the treatment (Eckhardt et al, 2004;Levesque et al, 2000;Scott, 2004;Scott & Wolf, 2003).…”
Section: Las Estrategias Motivacionales En Las Intervenciones Con Agrmentioning
confidence: 99%
“…Several meta-analyses conducted to evaluate the effectiveness of batterer intervention programs (BIPs) have indicated that the effect size of these interventions on reducing recidivism tends to be small (Arce et al, 2020;Babcock et al, 2004;Cheng et al, 2019;Eckhardt et al, 2013;Feder & Wilson, 2005;Smedslund et al, 2011). This limited success of BIPs in reducing recidivism has been attributed to different factors such as low treatment compliance and high dropout rates (Bennett et al, 2007;Daly & Pelowski, 2000;Jewell & Wormith, 2010;Lila et al, 2019;Olver et al, 2011), lack of motivation for change Crane et al, 2015;Eckhardt et al, 2008;Zalmanowitz et al, 2013), problems in building the working alliance (Cadsky et al, 1996;DiGiuseppe et al, 1994;Murphy & Baxter, 1997;Taft et al, 2004), and poor engagement in program activities (Musser et al, 2008;Taft et al, 2003).…”
mentioning
confidence: 99%
“…Despite limited empirical research into the validity of the TTM as it applies to the offending population, the model has been commonly utilised within correctional practice (Casey et al, 2005). The TTM has been used to evaluate behavioural change for substance abuse (D'Sylva et al, 2012), sexual offending (Tierney & McCabe, 2001), intimate partner violence (Gilchrist et al, 2015), general violence (Howells & Day, 2006), forensic mental health treatment (McMurran et al, 1998), juvenile males (Levesque et al, 2012) and motivational programmes (Anstiss et al, 2011;Yong et al, 2015). However, the appropriateness of applying TTM to this population has been debated (Anstiss et al, 2011;Austin, Williams, & Kilgour, 2011;Burrowes & Needs, 2009;Casey et al, 2005;Polaschek, Anstiss, & Wilson, 2010).…”
Section: Transtheoretical Modelmentioning
confidence: 99%